Theoretical and empirical foundations of the Deutsche Bundesbank's monetary targeting - Otmar Issing (Intereconomics, 1992)
Criticism of the course followed by the Deutsche Bundesbank has been increasing recently. Professor Dr. Otmar Issing explains the theoretical concept of German monetary policy and the basic principles of the Bundesbank's monetary targeting.
Keywords: 330